Diseño del sistema de gestión ambiental basado en la norma iso 14001:2015 en la empresa aspersores Colombianos ltda. (2021)
This research work arises from the need for the company Aspersores Colombianos Ltda to give continuity to the certification process that was in force until 2014, which caused the suspension of certain important activities for good environmental performance, generating disorganization and little commitment. by all the collaborators of the organization. This initiative aims to design an EMS based on the identification of environmental impacts related to the work areas and activities developed by the company. In the methodology, they were activities that negatively impact the environment in some way, generating additional costs. On the other hand, the design of environmental programs that reduce the identified impacts is proposed, the efficient energy saving program, efficient water saving program, comprehensive solid waste management program and sustainable purchasing program are established, this reflects the The organization's environmental commitment to carry out its economic activity responsible for the environment, so when you want to carry out its implementation, this research project is a reference for initial diagnosis and control.